Attitudes of preservice physical educators toward individuals with disabilities at University Parthenope of Napoli - Marco Di Nardo; Martin Kudláček; Domenico Tafuri; Jana Sklenaříková (Palacký University Olomouc, 2014)
Background: Inclusion refers to the notion that all students, regardless of disability (mild or severe), will be taught in regular education classes even if special resources are needed. Attitudes about inclusion are extremely complex and vary from country to country and school to school. One of the factors influencing the effective implementation of inclusion is the teacher's attitudes. The latest results from literature show that attitudes toward people with disabilities are changing in a positive direction over the last few decades. Objective: The purpose of this study was to examine the effects of an undergraduate adapted physical education course on the attitudes of pre-service physical educators toward individuals with disabilities. Methods: The Attitudes Towards Individuals with Physical Disabilities in Physical Education (ATIPDPE) instrument, based upon the Theory of Planned Behaviour (Ajzen, 1991) was used to measure the attitudes of pre-service teachers within three groups of students of the Department of Sport Science at the Università Degli Studi di Napoli "Parthenope" (Italy) enrolled in the 1st and 3rd year of Bachelor's studies in the Department of Sport Science, and students enrolled in the last year of a Master degree in Motor Activities and Preventive for Health. The software package SPSS 19.0 was used to analyze results via a Mann-Whitney U test and multiple regression analysis. Results: Although no significant differences between the groups were found in relation to group year or subject major, results found positive attitudes of pre-service teachers towards inclusion (Physical Education (PE) 1st year attitude (ATT) mean = 58.93; PE 3rd year ATT mean = 61.11; Postgraduate 2nd year mean = 59.80), as well as very high intentions. Attitudes were found to account for 30% of variance of intentions (R2 = .30). Conclusion: This research concluded that it is necessary to further improve and develop attitudes and intentions of pre-service teachers to ensure the implementation of successful inclusive physical education programs. In order to achieve this, university courses need to provide more effective courses and experiences relating to the teaching of students with disabilities.